MANF overexpression ameliorates oxidative stress-induced apoptosis of human nucleus pulposus cells by facilitating mitophagy through promoting MFN2 expression - Liang Ma; Xiangyu Meng; Tuerhongjiang Abudurexiti; Yuntao Liu; Jiang Gao; Weibin Sheng (Scientific Reports)
Abstract Intervertebral disc degeneration (IDD) is a degenerative condition associated with impaired mitophagy. MANF has been shown to promote mitophagy in murine kidneys; however, its role in IDD remains unexplored. This study aimed to elucidate the mechanism by which MANF influences IDD development through the regulation of mitophagy. Human nucleus pulposus (NP) cells were exposed to tert-butyl hydroperoxide (TBHP) to establish an oxidative stress-induced cellular model. The expression levels of MANF in NP cells were quantified using quantitative real-time PCR (qPCR) and Western blotting. The impact of MANF on TBHP-induced NP cells was evaluated by assessing cell viability, apoptosis, and the levels of mitophagy-related proteins. The underlying mechanisms were further investigated using RNA-binding protein immunoprecipitation (RIP), dual-luciferase reporter assays, qPCR, and Western blotting. Results indicated that MANF expression was significantly downregulated in both IDD patients and TBHP-induced NP cells. Overexpression of MANF inhibited apoptosis, enhanced cell viability, and promoted mitophagy in TBHP-treated NP cells. MFN2 was identified as a downstream target of MANF, and MANF overexpression upregulated MFN2 expression in NP cells, whereas TBHP markedly suppressed MFN2 expression. Furthermore, knockdown of MFN2 partially reversed the effects of MANF overexpression on apoptosis, cell viability, and mitophagy in TBHP-treated NP cells. Collectively, these findings demonstrate that MANF overexpression enhances mitophagy by upregulating MFN2 expression, thereby mitigating oxidative stress-induced apoptosis in NP cells. These results provide novel insights into the pathogenesis of IDD.